An open double ring antenna with multiple reconfigurable feature for 5G/IoT below 6GHz applications - Duong Thi Thanh Tu; Son Cao; Hien Duong (Bulletin of Electrical Engineering and Informatics, 2022)
In this paper, we proposed a hybrid or compound reconfigurable antenna using three PIN diode switching to achieve the different types of reconfiguration: frequency and radiation pattern. Based on an open ring structure with the varied active PIN diodes, the proposed antenna radiation pattern can scan a beam along with one of five directions with the same operating frequency. Depended on the number of active PIN diodes, the antenna operating frequency also can switch to two of six bands which are 1.9 GHz, 2.4/2.6 GHz, 3.5 GHz, 5 GHz, and 5.6 GHz. All frequency bands are popular ones of wireless communication as well as 5G/IoT applications. In addition, the antenna gets a compact size of 30mm *30 mm*1.6 mm and wide bandwidth due to using the radiating shape of a double ring. All details of antenna design are optimized by CST software, and the simulation results agree well with the measurement results.